MINI REVIEW: WIRELESS CHARGING SEBAGAI INOVASI PENGEMBANGAN TEKNOLOGI ELEKTROMAGNETIK DALAM MENUJU ERA SOCIETY 5.0 - Rezeki, Yulianto Agung; Zahra, Aisha; Kamilla, Amanda Alya; Ramadhani, Fadhila (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
The wireless charger is a technology that can transfer energy through an air gap without using cables. This technology is essential in welcoming other technological developments in industry 5.0 because of its effectiveness. However, the understanding and development related to wireless chargers are still very minimal, especially in Indonesia. Articles that review wireless chargers are also still very limited in number. Therefore, this article presents a review related to wireless chargers, the development of wireless chargers as electromagnetic applications, and describes the advantages and disadvantages of wireless chargers using the literature study method. The wireless charger is one of the topics discussed in electromagnetics material. Therefore, the information in this article can be used as a reference for educators in teaching students about electromagnetics material.